Prospects for chimeric antigen receptor-modified T cell therapy for solid tumors - Erhao Zhang; Jieyi Gu; Hanmei Xu (Molecular Cancer, 2018)
Abstract The potential for adoptive cell immunotherapy as a treatment against cancers has been demonstrated by the remarkable response in some patients with hematological malignancies using autologous T cells endowed with chimeric antigen receptors (CARs) specific for CD19. Clinical efficacy of CAR-T cell therapy for the treatment of solid tumors, however, is rare due to physical and biochemical factors. This review focuses on different aspects of multiple mechanisms of immunosuppression in solid tumors. We characterize the current state of CAR-modified T cell therapy and summarize the various strategies to combat the immunosuppressive microenvironment of solid tumors, with the aim of promoting T cell cytotoxicity and enhancing tumor cell eradication.